Effects of different periods of rapid weight loss on dehydration and oxidative stress - Nishimaki, M.; Tabata, H.; Konishi, M.; Pettersson, S.; Sakamoto, S. (Archives of Budo, 2018)
Background and Study Aim: Many athletes will lose weight 5% or more within 7 days. Many reports have been published on the negative health effects of rapid weight loss (RWL) in wrestlers. This study aims to examine the effects of different periods of RWL on dehydration state and oxidative stress.